Traditional knowledge and practices, sacred spaces and protected areas, technological progress: Their success in conserving biodiversity. Issue 5 (4th May 2022) - Parween, Rana; Marchant, Rob
Abstract: While the loss of species is a well‐known phenomenon drawing much attention, the loss of traditional ecological knowledge is more insidious and goes unnoticed. India, a mega‐biodiverse country, is home to many indigenous communities known for their historical conservation strategies entwined in traditional beliefs. Using focus groups, questionnaire surveys, in‐depth interviews, and in‐class test, this study explores the differences in knowledge and attitudes towards conserving biodiversity amongst four stakeholder groups living around two national parks in the state of Uttarakhand. Forest officers highlight lack of documentation of traditional practices and its coverage in school curricula. School children's test results show lowest scores in biodiversity amongst all science subjects. Village elders' responses show alienation, with some having to change their traditional means of livelihood due to environmental degradation. General public showed interest, awareness and admiration for ancestral ways of living in co‐existence with nature. Along with its ethical, cultural and societal dimensions, biodiversity plays a critical role in sustaining ecosystems and supporting livelihoods. In times of environmental uncertainty when the experiences of the living past may not be directly applicable, its recognition as a tried and tested inventory could be a beneficial resource that needs capturing before it is lost forever. Abstract : While the loss of species is a well‐known phenomenon drawing much attention, the loss of traditional ecological knowledge is more insidious and goes unnoticed. India, a mega‐biodiverse country, is home to many indigenous communities known for their historical conservation strategies entwined in traditional beliefs. In times of environmental uncertainty when the experiences of the living past may not be directly applicable, its recognition as a tried and tested inventory could be a beneficial resource that needs capturing before it is lost forever.